Mechanical properties of tungsten following rhenium ion and helium plasma exposure. (August 2017) - Corr, C.S.; O'Ryan, S.; Tanner, C.; Thompson, M.; Bradby, J.E.; De Temmerman, G.; Elliman, R.G.; Kluth, P.; Riley, D.
Highlights: Observation of increased hardness due to plasma and ion irradiation. Surface morphology changes determined by optical interferometry. Possible nanobubble formation investigated by grazing incidence small angle x-ray scattering. Nanobubble formation of 1nm diameter observed in high surface temperature tungsten subjected to pure Helium plasma. Abstract: Mechanical properties of Tungsten (W) samples irradiated with 2 MeV Rhenium (Re) ions and helium (He) plasma were investigated using nanoindentation. It was found that there was an increase in hardness for all samples following separate irradiation with both Re ion and He plasma. A slight increase in hardness was obtained for combined exposures. A comparable increase in hardness was observed for a pure He plasma with a sample temperature of 473 K and 1273 K. Optical interferometry was employed to compare surface modification of the samples. Grazing incidence small angle x-ray scattering confirmed He nano-bubble formation of approximately 1 nm diameter in the higher temperature sample, which was not observed with samples at the lower temperatures.